Self-control enhances vigilance performance in temporally irregular tasks: an fNIRS frontoparietal investigation - Mouloua, Salim Adam; Helton, William S.; Matthews, Gerald; Shaw, Tyler H. (Frontiers in Neuroergonomics, 2024)
The present study investigated whether trait self-control impacted operators’ behavior and associated neural resource strategies during a temporally irregular vigilance task. Functional near-infrared spectroscopy (fNIRS) readings of oxygenated hemoglobin (HbO2) and deoxygenated hemoglobin (HbR) from twenty-nine participants were recorded from the prefrontal and parietal cortices. Self-control was associated with better perceptual sensitivity (A’) in the task with the irregular event schedule. A left-lateralized effect of HbO2 was found for temporal irregularity within the dorsomedial prefrontal cortex, in accordance with functional transcranial doppler (fTCD) studies. Self-control increased HbR (decreasing activation) at right superior parietal lobule (rSPL; supporting vigilance utilization) and right inferior parietal lobule (rIPL; supporting resource reallocation). However, only rSPL was associated with the vigilance decrement – where decreases in activation led to better perceptual sensitivity in the temporally irregular task. Additionally, short stress-state measures suggest decreases in task engagement in individuals with higher self-control in the irregular task. The authors suggest a trait-state-brain-behavior relationship for self-control during difficult vigilance tasks. Implications for the study include steps towards rectifying the resource utilization versus allocation debate in vigilance – as well as validating HbO2 and HbR as effective constructs for predicting operators’ mental resources through fNIRS.